Global Launch Event For The CGIAR Initiative on National Policies And Strategies For Food, Land And Water Systems Transformation (NPS) Initiative: Presentation - Breisinger, Clemens; Nicol, Alan; Buisson, Marie-Charlotte; Xinshen Diao; Karachiwalla, Naureen; Maru, Joyce; Kassim, Yumna (International Food Policy Research Institute, 2022)
Slide deck from the Global Launch Event For The CGIAR Initiative on National Policies and Strategies for Food, Land and Water Systems Transformation (NPS), taking place in Kenya.